2021
DOI: 10.1111/jvh.13609
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, perception and expectation of management of hepatitis B infection among pregnant hepatitis B carriers in Hong Kong

Abstract: Lack of awareness regarding the risk of hepatitis B virus (HBV) infection and the interventions available during pregnancy among the pregnant carriers may influence their willingness and adherence to the management. This study assessed the knowledge, perception and expectation of HBV infection among pregnant HBV carriers in Hong Kong. A prospective multicentre cross-sectional questionnaire study was carried out between August 2019 and April 2021. The general knowledge on HBV, perception and expectation, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Indeed, only 34.75% of the HBsAg-positive pregnant women were aware that the HBV can be transmitted through the poor disinfection of tattoos, eyebrows and ear piercings, acupuncture, and unprotected sexual intercourse. A lack of knowledge and awareness about the HBV transmission route is consistent with the findings of previous studies in China and other HBV-endemic countries (13,(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, only 34.75% of the HBsAg-positive pregnant women were aware that the HBV can be transmitted through the poor disinfection of tattoos, eyebrows and ear piercings, acupuncture, and unprotected sexual intercourse. A lack of knowledge and awareness about the HBV transmission route is consistent with the findings of previous studies in China and other HBV-endemic countries (13,(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 89%
“…Chronic asymptomatic HBV carriers (ASCs) with HBeAg-negative are predominant among chronic ASCs, including women of childbearing age, and can also develop a potential risk of high morbidity due to HBV-related fatal liver diseases, mostly hepatocellular carcinoma and cirrhosis ( Kumar et al., 2009 ; Organization, 2016 ; Cui et al., 2022 ; Lian et al., 2022 ; Wang and Chen, 2022 ). Previous reports indicated that the levels of serum HBV-DNA, viral antigens (HBsAg, HBeAg) and ALT were mostly normal or stable in chronic ASCs with/without HBeAg-negative status, including pregnancy ( Cheung et al., 2021 ; Hsu et al., 2022 ; Wang et al., 2022 ). Our results showed that low HBV-DNA and ALT levels were not significantly different among HC, PW, and PW with HBeAg-negative ASCs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the awareness level of hepatitis B among residents must be determined when formulating relevant policies. In China, recent studies focused on pregnant women [7], medical workers [8], migrant workers [9], and other specific populations. There is lack of research among the general community residents, and the hepatitis B awareness level among Qingdao residents is still unknown.…”
Section: Introductionmentioning
confidence: 99%